2014
DOI: 10.1016/j.nicl.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based clustered imaging by multiparameter diffusion tensor images for glioma grading

Abstract: Gliomas are the most common intra-axial primary brain tumour; therefore, predicting glioma grade would influence therapeutic strategies. Although several methods based on single or multiple parameters from diagnostic images exist, a definitive method for pre-operatively determining glioma grade remains unknown. We aimed to develop an unsupervised method using multiple parameters from pre-operative diffusion tensor images for obtaining a clustered image that could enable visual grading of gliomas. Fourteen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 60 publications
0
62
0
1
Order By: Relevance
“…The leave-one-out cross validation (LOOCV) strategy, which is widely used in machine learning studies and allows the use of most training data, was applied to assess the performance of each classifier in our study [ 18 , 33 ]. Assuming the sample number is N , N -1 samples were selected as training data to construct the classifying model while the remained one sample was used as the testing data to testify the predicting accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leave-one-out cross validation (LOOCV) strategy, which is widely used in machine learning studies and allows the use of most training data, was applied to assess the performance of each classifier in our study [ 18 , 33 ]. Assuming the sample number is N , N -1 samples were selected as training data to construct the classifying model while the remained one sample was used as the testing data to testify the predicting accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…First, a subset of vital features that contribute most or are most relevant to glioma grading can be picked up with suitable feature selection methods [ 4 , 17 ]. Furthermore, the machine can automatically learn the discrimination patterns from the existing data and establish the corresponding model to predict the individual glioma grade [ 16 , 18 ]. Additionally, the classifying model can be further optimized to improve its diagnostic accuracy by selecting an appropriated classifier, optimizing model parameters or specific validation procedure [ 4 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple tensor metrics, including average diffusion coefficient (ADC), fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD), planar tensor (Cp), spherical tensor (Cs), and linear tensor (Cl) can be calculated from DTI ( Basser and Pierpaoli, 2011 ). However, although previous studies mainly demonstrated the role of ADC, FA, and MD in glioma imaging ( Stadlbauer et al, 2006 ; Inano et al, 2014 ; Davanian et al, 2017 ), few have investigated the value of the rest of the scalar parameters, including the AD, RD, Cp, Cs, and Cl values in gliomas grade diagnosis. ADC, FA, and MD in the tumor zone are useful for distinguishing glioma grades.…”
Section: Introductionmentioning
confidence: 99%
“…Several articles reported that pre-operative assessment with the DTI provided helpful information for neurosurgery. Continuously growing numbers of literature data indicate DTI is not only used for demonstration of fiber destruction by tumor invasion but also as a part of multiparametric assessment complex for differential diagnosis and tumor grading [12]- [15].…”
Section: Discussionmentioning
confidence: 99%